Constructive Thinking at the Tertiary Level of Education - Jolana Fedorková; Eva Kozáková; Ivana Nekvapilová (Communications of International Proceedings, 2021)
The aim of the authors of the article is to identify the level of the constructive thinking of future leaders in the field of studies of direct leadership and engineering-managerial specialists in the Army of the Czech Republic. The text informs about the results of the pilot quantitative research on the global constructive thinking of military university students at the end of studies. The concept of constructive thinking is appropriate to conclude in the content of the study lessons. In the research part was using the standardized questionnaire research technique – Constructive Thinking Inventory created by author Seymour Epstein. The results of the applied method describe the level and differences of global constructive thinking, emotional and behavioral coping, and categorical thinking by each participant. The research sample consisted of a total 91 military students of a five-year master's degree program, full-time study at the University of Defense in Brno. They are future officers and engineering specialists, whom after graduation of the study program is predetermined to serve in the Czech Armed Forces. No significant differences between the students of individual faculties and the Czech standardization sample were found out, although their focus is significantly different (technical fields versus economics and management). The results of it are going to be applied in the next period for suggestions and recommendations of interactive educational programs enhancing the competence of decision‑making. The outcomes are discussed in the context of the training of military students at the tertiary education of under the auspices of the Ministry of Defense in the Czech Republic.
Keywords: Constructive Thinking; Emotional / Behavioral Coping; Military Students; Tertiary / Military Higher Education.